2013
DOI: 10.1161/circulationaha.113.001742
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Hydroxylase Domain Protein 2 Plays a Critical Role in Diet-Induced Obesity and Glucose Intolerance

Abstract: Matsuura et al Role of PHD2 in Adipocytes 2079Several cell culture studies have revealed that hypoxia and HIF convert cell metabolism that is dependent on aerobic glucose oxidation and fatty acid synthesis into that which is dependent on anaerobic glycolysis. HIF not only upregulates a series of glycolytic enzymes 15,16 but also actively inhibits oxidative phosphorylation in mitochondria by inducing pyruvate dehydrogenase kinase 1 (PDK1).17,18 PDK1 inhibits pyruvate dehydrogenase activity and consequently redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 40 publications
9
68
5
1
Order By: Relevance
“…20 HIF-P4H-2 inhibition leads to improved lipid and glucose metabolism, reduced serum cholesterol levels, and protection from obesity and metabolic dysfunction. 9,21,22 We present evidence here that pharmacological and genetic HIF-P4H-2 inhibition also protects from atherosclerosis development.…”
Section: Discussionmentioning
confidence: 74%
“…20 HIF-P4H-2 inhibition leads to improved lipid and glucose metabolism, reduced serum cholesterol levels, and protection from obesity and metabolic dysfunction. 9,21,22 We present evidence here that pharmacological and genetic HIF-P4H-2 inhibition also protects from atherosclerosis development.…”
Section: Discussionmentioning
confidence: 74%
“…Currently, no explanation is available for the discrepancy between those data and the beneficial effects of Hif-a stabilization by Hif-p4h-2 deficiency, but the additional stabilization of Hif-2a has been suggested to possibly play an important role (25).…”
Section: Discussionmentioning
confidence: 98%
“…Mice with adipocyte-specific Hif-p4h-2 deletion also have less WAT, smaller adipocytes, a lower number of adipose tissue macrophages, and improved glucose tolerance (25); however, such changes were seen only in those fed an HFD, and no changes were reported in serum cholesterol levels, suggesting that Hif-p4h-2 deficiencies in several tissues play an important role in metabolic changes in Hif-p4h-2 gt/gt mice. Acute hepatic Hif-p4h-3 deletion has also been reported to improve glucose tolerance and insulin sensitivity, but no data were available on its effects on weight gain or serum cholesterol levels (26).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies on the role of PHD2 in this condition have suggested a detrimental role of this protein during obesity. While Matsuura et al131 observed that deletion of PHD2 in adipocytes attenuated weight gain and alleviated the glucose intolerance that occurs during a high-fat diet model, with reduced fat mass and lower macrophage infiltration into the white adipose tissue, Michailidou et al132 showed an increased adipose mass in adipose-specific PHD2-knockout mice. Notwithstanding the disparity in adipose mass, this group also observed a normal glucose tolerance in these mice, with reduced levels of circulating fatty acids and no increase in macrophage levels in the white adipose tissue 132.…”
Section: The Role Of Phd2 In Pathologymentioning
confidence: 99%